The breakdown of leaves of poplar and holm oak in three Moroccan streams : effect of burial in the sediment (Annales de Limnologie - International Journal of Limnology, 1999)
Weight loss of leaves of Populus nigra and Quercus ilex was observed in coarse-mesh bags exposed in three watercourses and their sediment (-30 and -50 cm) near the city of Fes. The watercourses were: Oued Sebou (a river), Oued Sidi-Harazem (issuing from a warm spring), and Ain Chkef (a cold spring). Weight loss was faster at the surface than within the sediment. Weight loss was faster in poplar than in the tough holm oak leaves. At all levels, weight loss was fastest in Oued Sebou where the water flowed faster both at the surface and within the coarser sediment. It was slowest in the cold spring. Thus the influence of leaf texture, current velocity, and temperature were stressed